Host response and peri-implantitis - Monica Grazieli CORRÊA; Suzana Peres PIMENTEL; Fernanda Vieira RIBEIRO; Fabiano Ribeiro CIRANO; Marcio Zaffalon CASATI
Abstract Considering the absence of predictable and effective therapeutic interventions for the treatment of peri-implantitis, scientific evidence concerning the host response profile around dental implants could be important for providing in the future a wider preventive and/or therapeutic window for this peri-implant lesion, indicating biomarkers that provide quantifiable measure of response to peri-implant therapy. Moreover, a better knowledge of pattern of host osteo-immunoinflammatory modulation in the presence of peri-implantitis could either benefit the early diagnostic of the disease or to cooperate to prognostic information related to the status of the peri-implant breakdown. Finally, new evidences concerning the host profile of modulators of inflammation and of osseous tissue metabolism around dental implants could explain the individual susceptibility for developing peri-implant lesions, identifying individuals or sites with increased risk for peri-implantitis. The focus of this chapter was, based on a systematically searched and critically reviewed literature, summarizing the existing knowledge in the scientific research concerning the host osteo-immunoinflammatory response to the microbiological challenge related to periimplantitis.